The Validaty and Practicality of Media for Teaching Atomic Bolls for Class X Students on the Material of Atomic Strubture - indang, indang -; Sabekti, Ardi Widhia; Adriani, Nina (Universitas Negeri Surabaya, 2019)
One effort to improve student learning outcomes is to choose teaching media that are appropriate and attract students' attention. The media developed is a three-dimensional ball teaching media.The purpose of this study is to develop three-dimensional atomic ball teaching media, to find out the validity level of three-dimensional atomic ball teaching media, to find out the practicalities of the three-dimensional atomic ball teaching media that have been developed. This research is a type of Research and Development (R & D) research using a 4D development model, namely define, design, develop, and dessiminatebut is limited to the develop stage. The teaching media developed were validated by media experts and material experts. The subject of this research trial was a chemistry teacher to find out the practicality of three-dimensional atomic balls teaching media, and 20 students of East Siantan 1 High School to find out the practicality of three-dimensional atomic balls. The method used to analyze data uses qualitative and quantitative descriptive techniques. The results showed that the validity of three-dimensional atomic ball teaching media for atomic structure material was obtained from the results of a media expert's assessment of 95.19% with very valid criteria, and the material expert's assessment was 81.23% with very valid criteria.The practicality test results were obtained from teacher responses of 92.5% with very practical criteria, and 81.41% student responses with very practical criteria. Based on the results of the study it can be concluded that atomic ball teaching media in three dimensions of atomic structure are worthy of being used as learning media by teachers and students.